The electrochemical oxidation of 5-thio-2-nitrobenzoic acid (TNBA) at a boron doped diamond electrode: Demonstration of a CEC reaction - Nekrassova, O; Lawrence, N; Compton, R (2003)
The oxidation of 5-thio-2-nitrobenzoic acid (TNBA) over a wide pH range has been investigated using cyclic voltammetry at a boron doped diamond electrode. The reaction has been shown to proceed via a CEC reaction process in which at lower pH the thiol moiety of the TNBA species has to undergo deprotonation before oxidation. DIGISIM modelling of the voltammetric profiles deduced a value of 5.2 for the pKa of the thiol moiety which is in good agreement with that obtained from spectrophotometric data. Also reported are the rate constants for all the heterogeneous and homogeneous processes.